Clinical Practice Guidelines for Bacterial Meningoencephalitis. - Belkys Rodríguez Llerena; Luciano Núñez Almoguea (Medisur)
Clinical Practice Guidelines for Bacterial Meningoencephalitis. It has been defined as an acute inflammatory process caused by bacteria, often purulent, which involves the meninges, subarachnoid space around the brain, spinal cord and usually includes the ventricles. It is caused in the 80% of the patients by three bacteria: Haemophilus influenzae, Neisseria meningitides and Streptococcus pneumonia. Concepts, classification, diagnosis and treatment were reviewed. It includes assessment guidelines focused on the most important aspects to be accomplished.